The rise of encrypted malware. Issue 5 (May 2019) - Yaacoubi, Omar
Abstract : Increasingly complex multi-cloud architectures and more stringent regulatory environments have increased reliance on encryption – primarily secure sockets layer (SSL) and transport layer security (TLS) – to the extent that over 80% of all network traffic is now encrypted. While in many ways the growth of encryption is a good thing for security, it also creates a backdoor for hackers and threat actors looking to hide from traditional detection tools. Organisations are adopting more stringent encryption practices. And while the growth of encryption might seem a good thing for security, it also creates a backdoor for hackers and threat actors looking to hide from detection tools. Additionally, as organisations continue to move to the cloud, increase their utilisation of APIs and adopt ever-more complex and sensitive systems, they find themselves with ever-more complex multi-cloud architectures. The solution lies in encrypted cognitive analytics, argues Omar Yaacoubi of Barac, which enables the creation of new types of data elements or telemetry that are independent of protocol details.